Treating lysosomal storage disorders: current practice and future prospects. - Platt, F; Lachmann, R (2009)
There are over 40 human disease states that are caused by defects in various aspects of lysosomal function. Over the past two decades there has been dramatic progress in the development and evaluation of therapies for lysosomal storage disorders, several of which are now in routine clinical use or in clinical trials. The greatest current challenge is in developing effective therapies for treating the CNS manifestations of these complex disorders. In this article, we will review the current therapies/approaches being considered for treating lysosomal storage diseases and give a perspective on the scientific, medical, social and ethical issues they raise.